The role of monocytes in ANCA associated vascultis - O'BRIEN, EÓIN (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2017)
ANCA associated vasculitis (AAV) encompasses several autoimmune conditions characterised by destruction of small vessels, inflammation of the respiratory tract, and glomerulonephritis. Most patients harbour autoantibodies directed against myeloperoxidase (MPO) or proteinase 3 (PR3). These antigens are found mainly in the lysosomes of neutrophils and monocytes and can be externalised when these cells are activated. Clinical and experimental data suggest that pathogenesis is driven by ANCA-mediated activation of neutrophils and monocytes. The function of monocytes in disease has been relatively understudied. Here, I investigated the role of monocytes in AAV. I first determined the relative proportion of monocyte subsets in patients, and found an increase in the proportion of intermediate monocytes in patients versus control individuals. I found that this subset preferentially expressed MPO and PR3 on their surface, and that the expression of PR3 is not associated with CD177 as it is in neutrophils. I also found that monocytes respond differently to antibodies directed against MPO and PR3, with anti-MPO but not anti-PR3 leading to increased IL-1β, IL-6 and IL-8 production. In concordance with the observed higher surface expression of MPO on intermediate monocytes, this subset produces the highest quantity of IL-1β in response to anti-MPO stimulation suggesting a potential role in ANCA vasculitis. Changes in cellular metabolism, particularly a switch to glycolysis, have recently been linked to activation of immune cells and to production of IL-1β. Therefore, I next investigated the metabolic profile of monocytes in response to ANCA stimulation. In contrast to their cytokine production, I found a similar increase in glucose uptake from both anti-MPO and anti-PR3 stimulated monocytes. This increase corresponded to an increase in glycolysis, as measured by Seahorse extracellular flux analysis, immediately following antibody treatment. Interestingly, only the anti-MPO treated cells increased oxidative phosphorylation 4hr post stimulation and these cells were also the only producers of IL-1β. These data suggest a potential differential activation of monocytes treated with ANCA compared to other inflammatory cell types. The final aspect of this work was attempting to induce disease in a humanised mouse model, and to study the effects of monocytes on disease pathogenesis in this in vivo setting. I was unable to effectively induce disease in this model. However, I have shown for the first time that distinct monocyte subsets are present in these mice. The presence of these subsets provides a future model for the study of these cells in an in vivo setting and may benefit research into other diseases along with AAV. Taken together, these data strongly support a role for monocytes in the pathogenesis of AAV and implicate changes in their cellular metabolism as a mechanism of activation. These metabolic pathways may therefore be potential targets for therapeutic intervention.
APPROVED
Keywords: Monocyte; ANCA